Pengaruh Struktur Modal dan Profitabilitas Terhadap Harga Saham di Bursa Efek Indonesia (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Industri Periode 2020-2023) - Nur Afifah Fauziah; Hurriyaturrohman .; Muhamad Nur Rizqi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The goal of this research is to determine how capital structure and profitability affect the stock value of industrial goods manufacturers that are listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. This research uses quantitative descriptive techniques. To evaluate secondary data, SPSS 26 was utilized from a sample of 52 industrial goods manufacturing companies over a four-year period. The findings indicate that profitability and capital structure both have a noteworthy and favorable impact on stock values. The profitability of the capital structure variable significantly and favorably affects stock prices, whereas the other variable has a negative and insignificant effect.